Key Drivers of Student Satisfaction in E-Learning: A Case Study of Higher Education at a Public University in Harbin, China - Heng, Song (Scholar: Human Sciences, 2025)
Purpose: The study investigates the influence of five independent variables (Student Engagement, Interactions, Digital Literacy, Perceived Quality, and Cognitive Absorption) on one dependent variable (Student Satisfaction with E-learning). Additionally, it aims to identify significant differences between variables. Research design, data, and methodology: The research employed the Index of Item-Objective Congruence (IOC) for validity and a Cronbach’s Alpha in a pilot test for reliability. Data was obtained from the target population using a quantitative methodology and a questionnaire. Eighty valid responses from students at Harbin University were analyzed by multiple linear regression to verify the significant relationship between variables. Following this, all students from the research population implemented the 20-week strategic plan. Two types of tactics were used: behavioral interventional tactic and collaborative interventional tactic. Afterward, the quantitative results from post-SP and pre-SP were analyzed in the paired-sample t-test for comparison. Results: In multiple linear regression, the study revealed that student engagement, interactions, digital literacy, perceived quality, and cognitive absorption significantly impacted students’ satisfaction with E-learning. Finally, the results from the paired-sample t-test for comparison demonstrated a significant difference in students’ satisfaction with E-learning between the post-SP and pre-SP stages. Conclusions: This study aimed to help school administrators address questions about E-learning and analyze the factors affecting student satisfaction with E-learning courses at a public university in Harbin, China.